2003
DOI: 10.1021/ol0359517
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Asymmetric Preparation of Ketene Dimers from Acid Chlorides

Abstract: [reaction: see text] The cinchona alkaloid-catalyzed dimerization of monosubstituted ketenes generated in situ from the reaction of acid chlorides and diisopropylethylamine yields ketene dimers in high yields and enantioselectivities. This reaction tolerates sterically demanding and functionally diverse substituents. Kinetic studies suggest that the rate-determining step for the reaction is the deprotonation of the acid chloride by the tertiary amine to form ketene and that the stereochemistry-forming step is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 11 publications
6
54
1
Order By: Relevance
“…235 For determining yield and enantiomeric purity, the researchers immediately converted the volatile and unstable methylketene dimers into β-ketoamides 440. Kinetic studies suggested that the rate-determining step for the reaction is the deprotonation of the acid chloride by the tertiary amine to form the ketene.…”
Section: Aldol-lactonization Reactions In Nucleophilic Base Catalysismentioning
confidence: 99%
“…235 For determining yield and enantiomeric purity, the researchers immediately converted the volatile and unstable methylketene dimers into β-ketoamides 440. Kinetic studies suggested that the rate-determining step for the reaction is the deprotonation of the acid chloride by the tertiary amine to form the ketene.…”
Section: Aldol-lactonization Reactions In Nucleophilic Base Catalysismentioning
confidence: 99%
“…Dimerization of methylketene is catalyzed by an amine, trimethylsilylquinine, to give the b-lactone enantioselectively (Scheme 27) [129]. The catalyst amine attacks the ketene to form an ammonium enolate, an electron donating alkene.…”
Section: Catalyzed Dimerizationsmentioning
confidence: 99%
“…In particular, the use of cinchona alkaloids has been successfully applied in various organocatalytic transformations. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] To the best of our knowledge, there has been no report on the organocatalytic asymmetric cyclization of general isocyanoacetates and imines, although several examples can be used for references. Jorgensen et al performed the highly enantioselective and diastereoselective Mannich reaction of a-aryl-substituted cyanoacetates and N-Bocprotected a-amino esters with cinchona alkaloid 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When the catalyst loading was varied from 20 to 5 mol %, a decrease in yield but comparable enantioselectivity could be observed (entries [16][17][18]. To balance both the yield and the selectivity, we chose 10 mol % as the catalyst ratio.…”
Section: Introductionmentioning
confidence: 99%